Parâmetros do Manual Esfera em WASH no Assentamento Informal Yakera Ine - Bezerra, Giovana Adélia Ausier Oliveira (2023)
Since 2017, Venezuelan refugees have been living in Roraima state, Brazil. They are vulnerable, and according to the number of people arising, different types of settlement emerge such: as informal, and formal. Multiple stakeholders are supporting these vulnerable groups to improve their lives. The Venezuelan indigenous flow also increased in Roraima State, in Boa Vista city, they have been living since 2017 to 2022 in Pintolandia Shelter, and after this vulnerable group was moved to the indigenous Shelter Waraotuma a Tauranoko, however part of the population decided to stay in the past Shelter (Pintolandia), that is now denominated informal settlement/spontaneous occupation Yakera Ine. In Brazil, the lack of adequate sanitation or the wrong perception of it by the local community could carry out diseases related to health. For humanitarian crises, in collective Spaces related to settlement, exist minimal international humanitarian standards, which are pointed out in the Sphere Handbook and aim to protect and guarantee the right to access water and sanitation. In the humanitarian relief context, the acronym WASH means Water, Hygiene, and Sanitation. The WASH standards in Sphere are by the national Brazilian politics of water resources and correlated to Sustainable Development Goals from ONU. To understand the situation regarding sanitation in which the vulnerable community of the informal settlement Yakera Ine lives, the WASH parameters were identified according to the applicable Sphere Handbook for the informal settlement and verified which ones are by these standards in the settlement. The verification found a lack of water in the external bathrooms, and pending maintenance making the use of devices unfeasible, several points of accumulation of still water, both coming from the tap points by the shelter and laundry, as well as from a sewage pit overflowing with black water and lack of adequate waste disposal, and open defecation. This vulnerable group can be severely affected by sanitation-related diseases if it fails to manage some of the problems identified in this study, especially during the rainy season. A highlight is also the amount of solid waste spread throughout the occupation, which will also tend to worsen with the issue of the rain season. Based on the identified problems, a sanitation booklet was created for the target population to manage better water resource.